Biomimetic Superhydrophobic/Superoleophilic Highly Fluorinated Graphene Oxide and ZIF-8 Composites for Oil-Water Separation - Jayaramulu, Kolleboyina; Datta, Kasibhatta Kumara Ramanatha; Rösler, Christoph; Petr, Martin; Otyepka, Michal; Zboril, Radek; Fischer, Roland A. (Angewandte Chemie International Edition, 2016)
Superhydrophobic/superoleophilic composites HFGO@ZIF‐8 have been prepared from highly fluorinated graphene oxide (HFGO) and the nanocrystalline zeolite imidazole framework ZIF‐8. The structure‐directing and coordination‐modulating properties of HFGO allow for the selective nucleation of ZIF‐8 nanoparticles at the graphene surface oxygen functionalities. This results in localized nucleation and size‐controlled ZIF‐8 nanocrystals intercalated in between HFGO layers. The composite microstructure features fluoride groups bonded at the graphene. Self‐assembly of a unique micro‐mesoporous architecture is achieved, where the micropores originate from ZIF‐8 nanocrystals, while the functionalized mesopores arise from randomly organized HFGO layers separated by ZIF‐8 nanopillars. The hybrid material displays an exceptional high water contact angle of 162° and low oil contact angle of 0° and thus reveals very high sorption selectivity, fast kinetics, and good absorbencies for nonpolar/polar organic solvents and oils from water. Accordingly, Sponge@HFGO@ZIF‐8 composites are successfully utilized for oil–water separation. Pores for effect: The superhydrophobic and simultaneously superoleophilic HFGO@ZIF‐8 composites were utilized for oil–water separation. In this material zeolitic imidazolate (ZIF) nanocrystals serve as pillars between nanosheets of highly fluorinated graphene oxide.